USP8 inhibition regulates autophagy flux and controls Salmonella infection - Santelices, John; Ou, Mark; Maegawa, Gustavo H. B.; Hercik, Kamil; Edelmann, Mariola J. (Frontiers in Cellular and Infection Microbiology, 2023)
Ubiquitination constitutes a critical post-modification regulating essential cellular processes, including functions of innate immune cells. This protein modification is removed by enzymes called deubiquitinases. We used an activity-based proteomics screen in human macrophages to identify deubiquitinases regulated in macrophages during infection with Salmonella Typhimurium and Yersinia enterocolitica. USP8 was one of the deubiquitinases down-regulated upon Salmonella infection. Pharmacological inhibition of USP8 was associated with decreased bacterial survival within the macrophages. Moreover, inhibition of USP8 led to the downregulation of p62 autophagy adaptor, suggesting the distinct role of USP8 in regulating autophagy during Salmonella infection. These studies uncover a novel role of USP8 in the restriction of intracellular bacteria via modulation of the autophagy flux.